Male sex increases mortality in ventricular tachyarrhythmias - Weidner, Kathrin; Behnes, Michael; Rusnak, Jonas; Schupp, Tobias; Hoppner, Jorge; Taton, Gabriel; Reiser, Linda; Kern-Bollow, Armin; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Kuche, Philipp; et al. (Internal medicine journal, 2019)
BACKGROUND: Ventricular tachyarrhythmias are still associated with poor clinical outcomes. Therefore, it is important to stratify high-risk patients presenting with ventricular tachyarrhythmias for their individual risk of future outcomes. - AIM: To assess the impact of male sex on survival in patients presenting with ventricular tachyarrhythmias. - METHODS: All consecutive patients surviving ventricular tachycardia (VT) and fibrillation (VF) on admission from 2002 to 2016 were included and stratified according to sex differences by propensity score matching. The primary prognostic end-point was all-cause mortality at 30 months. Secondary end-points were all-cause mortality at 30 days, at index hospitalisation, after discharge, the composite of recurrent ventricular tachyarrhythmias and appropriate implantable cardioverter defibrillator (ICD) therapies, and finally rehospitalisation related to ventricular tachyarrhythmias. - RESULTS: A total of 784 (392 males and 392 females) matched patients was included. The rate of VT and VF was similar in both groups (VT: male 65% vs female 62%; VF: male 35% vs female 38%). Male sex was independently associated with the primary end-point of all-cause mortality at 30 months (31% vs 23%; hazard ratio (HR) = 1.432; 95% confidence interval (CI) 1.089-1.883; P = 0.010) as well as with the secondary end-point of all-cause mortality at index hospitalisation (mortality rate 31% vs 23%; log-rank P = 0.010; HR = 1.432; 95% CI 1.089-1.883; P = 0.010; mortality rate 10% vs 15%; HR = 1.685; 95% CI 1.117-2.542; P = 0.013). No differences in further secondary end-points were found. Sex differences of the primary end-point were predominantly observed in patients with VT at index (mortality rate 28% versus 20%; HR = 1.512; 95% CI 1.040-2.189; P = 0.028), without an ICD and with left ventricular ejection fraction ≥35% (log-rank values, P < 0.05). - CONCLUSION: Males presenting with ventricular tachyarrhythmias on admission were associated with higher all-cause mortality at 30 months and all-cause mortality at index hospitalisation.
First published: 27 November 2018
Gesehen am 02.07.2019